Sistem Informasi Penjualan Handphone Dan Accessories Pada Toko Nisa Ponsel Berbasis Web - Aini, Putri; Purnama, Iwan; Irmayani, Deci; Harahap, Syaiful Zuhri (Journal of Computer Science and Information System(JCoInS), 2020)
The Nisa Ponsel store still uses a recording system on the general ledger in the process of calculating the stock of incoming goods, sales transactions, and transaction reports, it is very possible that there will be greater errors starting from the stock of goods that are not the same in the warehouse, reporting that is not in accordance with the goods sold. To overcome these problems it is necessary a web-based system as one solution for it is necessary to optimize the use of computer data processing with the design of an information system that is applied to the PHP programming language and MySQL database in order to solve the problems that exist by being able to answer the needs of the company. The purpose of this study was made to analyze the problems in the mobile phone Nisa stores that still use recording on the ledger. It is expected that the system built later is really able to overcome the problems caused and able to improve performance more effectively and efficiently in data management and transactions.